Exploring axionlike particles beyond the canonical setup - Alonso Álvarez, Gonzalo; Jaeckel, Joerg (Physical review, 2018)
Axionlike particles (ALPs) are interesting dark matter candidates from both the theoretical and the experimental perspective. Usually they are motivated as pseudo-Nambu-Goldstone bosons. In this case one of their most important features is that their coupling to other particles is suppressed by a large scale, the vacuum expectation value of the field breaking the symmetry that gives rise to them. This naturally endows them with very weak interactions but also restricts the maximal field value and therefore the regions where sufficient dark matter is produced. In this paper we investigate deviations from this simplest setup, where the potential and interactions are as expected for a pseudo-Nambu-Goldstone boson, but the kinetic term has singularities. This leads to a significantly increased area in parameter space where such particles can be dark matter and can be probed by current and near future experiments. We discuss cosmological limits and in the course of this give a simple derivation of a formula for isocurvature fluctuations in models with general anharmonic potentials. As an application of this formula we give an update of the isocurvature constraints for QCD axion dark matter models, using the most recent results for the QCD topological susceptibility and the newest Planck data.